Malaysia, Singapore and Asean in an age globalisation - Khairulmaini Osman Salleh; Kong, Lily; Malaysia-Singapore Forum (8th : 2002 : Universiti Malaya) (Kuala Lumpur : Faculty of Arts and Social Sciences, University of Malaya, 2002)
PSZJBL